THE POTENTIAL BENEFITS OF NURTURING NATURE TO RESOLVE OVEREMPHASIZED STEM EDUCATION IN THE INDIAN EDUCATION SYSTEM - Mahmood, Rahil Riad; Park, Jiwoon (PEOPLE: International Journal of Social Sciences, 2018)
This study investigates STEM education in India in context of the nature-nurture debate. Discussed are the benefits of nurturing unique talents, rather than forcing subject choices and how the Indian education system has produced engineers who, due to societal biases, have been unable to acquire jobs. In an effort to validate the advantage of nurturing unique talents, a survey was conducted and the driving factors for specific professions identified. Three groups were included: high school students, professionals in non-engineering fields, professional engineers or engineering students. Each group was asked questions on their job/major and the role their family played in influencing choices. Results revealed that 90.6% of students had parents who wanted them to pursue STEM subjects for job security and due to societal pressure. Less than 10.7% confirmed that their parents urged them to pursue the Humanities. Of the professional engineers, 73.5% stated their calling didn’t lie in engineering and therefore planned on switching fields. Further case studies support that there exists a bias towards STEM education in India and that allowing students to nurture their unique nature might have benefits to both individuals and society.